Design of Midi Drum Controller Using Piezoelectric and Arduino-Based TCRT5000 Sensor to Facilitate Sound Engineer Performance in the Music Industry - Mirza Maulana; Kartika Kartika; Asran Asran; Misbahul Jannah; Arnawan Hasibuan; M Mursalin; Waleed Khalid Ahmed Al-Ani; Muzamir Isa (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
This study discusses the Midi Drum Controller using the Arduino Mega which has many analog pins making it suitable for producing complete drum pads as well as piezoelectricity which is used to detect vibrations when the drum pad is beaten, as well as the Tcrt5000 sensor which is used to control the hi-hat so that it can move. from the sound of an open hi-hat to a closed hi-hat. The results of this study indicate that piezoelectricity can detect vibrations and dynamics of strong and weak drum beats and send the game to midi-based virtual drum applications. The Tcrt5000 sensor used can also work well, judging by the sound it produces and the data sent when the Tcrt5000 sensor is on and off.